Effect of gratification on user attitude and continuance use of mobile payment services: a developing country context - Alhassan, Muftawu Dzang; Kolog, Emmanuel Awuni; Boateng, Richard (Journal of systems and information technology)
Purpose This study aims to investigate the gratifications driving the attitude and continuance use of mobile payment services in developing country context, such as Ghana. Also, the moderating effect of income and education on gratifications and attitude of users is explored. Design/methodology/approach Data was collected from conveniently sampled 361 users of mobile payment services in Ghana. A questionnaire, which mainly contains five-point Likert scale questions, was used to collect the data. The study adopted the Uses and Gratification (U&G) theory, where income and education were used as moderating factors. The data was analysed with SmartPLS for Structural Equation Modelling. Findings Among the other factors from the U&G theory, integrative, ease of use and usefulness gratifications were found to significantly influence attitude towards the use of mobile payment services in Ghana. In addition to this finding, user attitude significantly influences the continuance use intention of mobile payment services. Furthermore, the study revealed various effects of the moderating factors. These findings suggest that promoting mobile payment technology inclusiveness by creating a favourable environment would enhance the use of mobile payment services in Ghana. Research limitations/implications Given that this study was conducted in Ghana, a developing country, it is difficult to generalize the results to encompass the developed economies. In future, similar research should compare the developed and developing economies by considering culture as a moderating effect. Practical implications This study intends to provide information on the gratifications that drive the attitude and continuance use of mobile payment services in Ghana. The findings seek to augment mobile money service providers’ capabilities by providing them with an understanding of user gratification experience on mobile payment services. Additionally, the study will serve as a guide to policymakers in the government, telecommunication companies and mobile banking providers, to improve customer intimacy and gratification through their user behaviour. Originality/value Previous studies on user gratification have primarily focussed on the functional benefits derived from mobile payments and how they influence the service’s adoption. This study has contributed to literature by considering both the functional and non-functional benefits of mobile payment in developing country context. To the best of the